Whistleblowing System: Alarm Transparency And Bumn Accountability - Ririn Breliastiti; Temy Setiawan; Tiwi Herninta; Nasya Lita Natalsya (Information Technology and Science (ITScience), 2025)
Long-term business continuity is the expectation of every stakeholder. Therefore, good governance is the key to success that needs to be maintained and considered. Improving good governance requires the role of every internal and external stakeholder. Whistleblowing system (WBS) is an early alarm for system gaps and failures that cause disadvantages to the company. However, implementing WBS in Indonesia is a challenge for companies. The purpose of this study is to examine the implementation of WBS in Indonesian SOEs based on transparency and accountability in line with corporate governance including: delivery mechanism, media, number of reports, related parties, sanctions and institutional cooperation. This research is a qualitative research with a case study of 6 BUMN companies in the infrastructure sector in Indonesia in 2023. The data source used is secondary data in the form of annual reports with document study techniques and content analysis. Although WBS in Indonesia, especially infrastructure sector SOEs, has been carried out well and according to procedures and has clear regulations and laws, but protection of whistleblowers, organizational culture, the role of regulators, future prospects are still a challenge for SOEs in Indonesia today which requires special attention from companies, regulators, academics and society itself.